Karl Marx: From the Critique of Religion to the Critique of Politics - BOUHAFS, Fahima (Journal of Human Sciences, 2020)
We attempt in this paper to follow the critique taken by K.Marx towards religion and politics. The author begins this path by criticizing religion which he considers it as the space where a men dream of realizing their happiness which their real world could not provide. Throught criticism, K.Marx concludes that religion is the set of representations by means of which the dominant class legitimizes its position. In this context, to liberate man from religion means revolution against the state which uses religion to fulfil its material needs. The ability of the philosopher to provide solutions that liberate individuals from injustice and exploitation, and enable them to realize justice and real happiness is conditioned by how much he is involved in the real life.